Preparation of Chlorpheniramine Maleate-loaded Alginate/Chitosan Particulate Systems by the Ionic Gelation Method for Taste Masking - Jelvehgari, Mitra (DOCS, 2014)
BACKGROUND: Chlorpheniramine maleate (CM) is widely used as an antihistaminic drug but it is very bitter and as yet no mouth dissolving/disintegrating taste-masked preparation that might be useful for pediatric and geriatric patients is available in the market. OBJECTIVES: The purpose of this research was to mask the bitter taste of CM by formulating microspheres of the taste-masked drug. MATERIALS AND METHODS: This work was done to develop alginate/chitosan particles prepared by ionic gelation (Ca(2+) and Al(3+)) for the CM release. The effect of different chitosan and Ca(2+) concentrations on taste masking and the characteristics of the microspheres were investigated. Ca(2+) and Al(3+) alginates microspheres of CM were prepared using cross-linked insoluble complexes that precipitate, incorporating the drug. Formulations were characterized for particle size and shape, entrapment efficiency, fourier transform spectroscopy (FTIR), x-ray diffraction (XRD), and differential scanning calorimetry (DSC), bitter taste threshold and in vitro drug release in simulated gastrointestinal fluids. RESULTS: FTIR, XRD and DSC demonstrated unstable characters of CM in the drug-loaded microspheres and revealed an amorphous form. Also, the peak of alginate microparticles (Ca(2+) and Al(3+) ions) in all formulations remained the same, with low intensity of spectrum. The results of DSC, X-ray diffraction and FTIR showed the presence of several CM chemical interactions with alginate and ions (Ca(2+) and Al(3+)). The microsphere formulations showed desirable drug entrapment efficiencies (62.2-94.2%). Calcium/aluminum alginate retarded the release of CM at low pH = 1.2 and released the drug from microspheres slowly at pH = 6.8, simulating intestine pH. The drug release duration and the release kinetics were dependent on the nature of the polymers, the cation concentrations, and valences (Ca(2+) and Al(3+)). The drug release rate was decreased by an increase in chitosan and cation concentrations. CONCLUSIONS: The results of the present study indicated that oral preparation of CM with an acceptable taste is feasible.